ANTHROPOMORPHIC ROBOTIC HEAD –THREE PRELIMINARY APPROACHES - Beniamin CHETRAN; Vasile Sergiu JISA; Andras ERLI; Dan MANDRU (Fiabilitate şi Durabilitate)
The first part of the paper is dedicated to a study regarding the humans’ emotive facial expressionsand comparative analysis of representative examples of humanoid robotic heads. The authors’ contribution inthis field consists in three different proposals of anthropomorphic robotic head. All technical details that lead toour original design are presented, including the hardware structure, the actuation systems and control of therobotic systems.